EFFECTIVENESS OF COLD WATER COMPRESS AND WARM WATER COMPRESS TO PAIN IN PRE ELDERLY WITH OSTEOARTHRITIS (Studies in the village of the District Kepuh Kembeng Peterongan Jombang East Java Province) - Anis Kurniah; M. Zainul Arifin; . Suhardono (STIKES Insan Cendekia Medika Jombang, 2012)
Pain is the main complaint that is often felt by patients with osteoarthritis. Many alternatives that can be used to reduce pain, one of which is a non-pharmacological method that compresses cold water and warm water compresses. The purpose of this study was to compare the effectiveness between compress cold water and warm water compresses in reducing osteoarthritis pain. This research is pre experiment with one group pre and post-test design. The population is all pre elderly aged 50-65 years with osteoarthritis in Kepuh Kembeng village of 20 people. The sampling technique used is total sampling with instruments such as the observation sheet. Data presented in tables and analyzed using paired-simple T test and Mann Whitney Test. In the cold water compress obtained the highest pain scale before the therapy is severe pain (30%) and moderate pain (30%), after therapy becomes moderate pain (40%). In the warm water compress therapy group obtained the highest pain scale before treatment is moderate pain (60%), after treatment becomes mild pain (70%). Results of simple paired T-test on cold compresses obtained p = 0.000 and p = 0.02 in warm water compresses H1 accepted meaning. While the difference between using a different test Mann Whitney Test was obtained p = 0.667, the p> 0.05. The conclusion was that there was no significant difference between cold water compresses and warm water compresses to pain in pre elderly with osteoarthritis.